Combined papillary muscle sling and ring annuloplasty for moderate‐to‐severe secondary mitral regurgitation. Issue 11 (12th September 2016) - Mihos, Christos G.; Capoulade, Romain; Yucel, Evin; Melnitchouk, Serguei; Hung, Judy
Abstract: BACKGROUND: There is a 30–60% incidence of recurrent mitral regurgitation (MR) after mitral valve annuloplasty (Ring) for secondary MR. A concomitant papillary muscle sling (Ring+Sling) may improve valve repair by providing a more physiologic geometry of the mitral apparatus. METHODS: We retrospectively identified 58 consecutive patients with moderate‐to‐severe secondary MR who underwent a Ring+Sling repair, between March 2008 and May 2015. A Ring+Sling consisted of combined annuloplasty and papillary muscle approximation, utilizing a 4‐mm polytetrafluoroethylene graft placed around the base of each muscle. Comparison of echocardiographic variables with patients who underwent a Ring only was performed utilizing 2:1 propensity‐score matching (Ring+Sling = 34; Ring = 17). RESULTS: The baseline demographics were similar between the groups. The mean time to follow‐up echocardiogram was 10.1 months (range 0.25–42 months). At follow‐up, a Ring+Sling repair was associated with a lower mitral valve tenting height (p = 0.005), mitral valve tenting area (p = 0.009), and interpapillary muscle distance (p = 0.001); a smaller posterior leaflet tethering angle (p = 0.003); and a greater leaflet coaptation length (p = 0.002), when compared with Ring only. Recurrence of moderate or greater MR occurred significantly less in the Ring+Sling group (14.7%), as compared with Ring only (35.3%) (p < 0.001). Finally, actuarial survival at three years was 87% for Ring+Sling, and 82% for Ring only (p = 0.49). CONCLUSIONS: A Ring+Sling for secondary MR results in favorable changes in the mitral valve apparatus geometry, and is associated with less MR recurrence in the early postoperative period. Longer‐term follow‐up is needed to assess its durability and effects on left ventricular remodeling and survival.